The reassuring effect of firms' technological innovations on workers' job insecurity - Mauro Caselli; Andrea Fracasso; Arianna Marcolin; Sergio Scicchitano (Global Labor Organization (GLO), 2021)
We analyse how the adoption of technological innovations correlates with workers' perceived levels of job insecurity, and what factors mediate such relationship, by exploiting a recent, large and dedicated survey distributed to a representative sam- ple of Italian workers. The dedicated survey allows us to look at both cognitive and affective job insecurity as well as different technological innovations actually adopted by the companies where the workers are employed. The results show that the adoption of technological innovations by companies is related to a reduction in the level of job insecurity perceived by their workers and suggest that technological innovation is perceived by active workers as a signal of firms' health and of their commitment to preserving the activity. We also find that the reassuring effect of technological innovations is differentiated across companies and workers, due to the mediating role played by a number of factors, such as specific training and signifi- cant changes in workers' usual activities.
Keywords: J28; O33; 330; job insecurity; technology; innovation; automation